2012
DOI: 10.1099/mic.0.062943-0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the genes involved in the secretion and self-immunity of lacticin Q, an unmodified leaderless bacteriocin from Lactococcus lactis QU 5

Abstract: Lacticin Q (LnqQ) produced by Lactococcus lactis QU 5 is an unmodified linear bacteriocin, which is synthesized without an N-terminal leader peptide. In vitro synthesis and in vivo expression of LnqQ have revealed the intracellular toxicity of this leaderless peptide, as well as the necessity of a dedicated secretion and self-immunity system of producer cells. Further DNA sequencing and analysis have discovered 11 putative orf genes at the LnqQ locus. None of the orf genes showed similarities to any of the bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Co-expression of lnqQ and lnqBCDEF in a lactococcal heterologous host allowed the extracellular production of lacticin Q. 42) In addition, expression of lnqBCDEF rendered host cells immune to lacticin Q, and the expression of lnqQ alone revealed the intracellular toxicity of this leaderless peptide. Leaderless bacteriocins such as lacticin Q have intracellular toxicity, since they have no leader sequence to make bacteriocins inactive.…”
Section: Structural Determination and Characterization Of Novel Lmentioning
confidence: 99%
“…Co-expression of lnqQ and lnqBCDEF in a lactococcal heterologous host allowed the extracellular production of lacticin Q. 42) In addition, expression of lnqBCDEF rendered host cells immune to lacticin Q, and the expression of lnqQ alone revealed the intracellular toxicity of this leaderless peptide. Leaderless bacteriocins such as lacticin Q have intracellular toxicity, since they have no leader sequence to make bacteriocins inactive.…”
Section: Structural Determination and Characterization Of Novel Lmentioning
confidence: 99%
“…LnqD, the largest ORF (432 aa) in the lnqQ locus, has some homology to the membrane protein (486 aa) of Lactobacillus buchneri (25% identity) and the YdbT homolog protein (484 aa) of Leuconostoc pseudomesenteroides (23% identity). Previous work has revealed that a set of lnqBCDEF confers the secretion and self-immunity of LnqQ; however, the role of each gene product has not been elucidated (4). Thus, in this study, comprehensive gene disruption was carried out to determine the necessity of each gene and to deduce its role in LnqQ biosynthesis.…”
mentioning
confidence: 99%
“…The genes necessary for bacteriocin production and immunity are located near the structural gene and are generally arranged as an operon (1,2). Lacticin Q (LnqQ), produced by Lactococcus lactis QU 5 (3), is an unmodified leaderless bacteriocin that has a unique gene cluster (lnqBCDEF) following the structural gene (lnqQ) (4). As predicted in silico, lnqEF encodes an ATP-binding cassette (ABC) transporter with LnqE as the membrane-spanning domain and LnqF as the cytoplasmic ATPase domain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Assessment of possible intracellular accumulation of the Ent53B precursor peptide was done using the previously reported method with slight modifications [31,32]. Briefly, recombinant strains showing negative Ent53B bioactivity were precultivated in GM17 containing 10 µg ml À1 cm at 30 C overnight and sub-cultured into fresh medium containing the same antibiotic with the same culture conditions for 7 h. Cells were then harvested by centrifugation, washed with 50 mM Tris-HCl (pH 7.4), and resuspended in 500 µl of the same buffer.…”
Section: Detection Of Possible Intracellular Accumulation Of Ent53b Pmentioning
confidence: 99%